Comparative Analysis of Financial Performance PT. Berkah Beton Sadaya Tbk And PT. PAM Mineral Tbk - Fitria, Nita; Winanda, Heru Prasetyo (Rangkiang: Journal of Islamic Economics and Business, 2024)
The aim of this research is to analyze the financial performance of PT Berkah Beton Sadaya Tbk and PT PAM Mineral Tbk using the liquidity ratio, solvency ratio and profitability ratio methods. The type of research is quantitative descriptive. The data source used is a secondary data source. The data analysis method used is the time series analysis method, namely comparing financial performance from the previous year, and also using cross section analysis, namely comparing the company's performance with similar companies. The research results show that the financial performance is as follows: Based on the calculation results of the liquidity ratio, it shows that the financial performance of PT Berkah Beton Sadaya Tbk has been able to fulfill its obligations (debt) in the 2019-2022 period and continues to increase every year. In general, PT Berkah Beton Sadaya Tbk is better in debt management and solvency compared to PT PAM Mineral Tbk. Overall, PT Berkah Beton Sadaya Tbk showed consistency in its profitability performance from 2019 to 2021, although it experienced a slight decline in 2022. Meanwhile, PT PAM Mineral Tbk experienced larger fluctuations in several ratios, and its best performance occurred in 2022 . Comparison between the two shows that PT Berkah Beton Sadaya Tbk tends to be better in maintaining its profitability during this period